2016
DOI: 10.1007/s11760-016-0881-x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive reversible video watermarking based on motion-compensated prediction error expansion with pixel selection

Abstract: In this study, a motion-compensated prediction error expansion-based adaptive reversible video watermarking algorithm is proposed. Blocks of motion-compensated frames are classified as smooth and non-smooth according to their prediction errors. Unlike the current reversible video watermarking methods that apply a single watermarking strategy to all blocks, the proposed method uses two different strategies for smooth and non-smooth blocks. This adaptive strategy is shown to increase watermarking capacity. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Author achieved the better robustness and channel capacity using the proposed approach. Vural et al [12] have identified the motion compensated frames based on the smoothness exist within continuous video frames. The block adaptive evaluation was also conducted to identify the pixel distortion and use it as the cover pixel for effective data hiding within videos.…”
Section: Related Workmentioning
confidence: 99%
“…Author achieved the better robustness and channel capacity using the proposed approach. Vural et al [12] have identified the motion compensated frames based on the smoothness exist within continuous video frames. The block adaptive evaluation was also conducted to identify the pixel distortion and use it as the cover pixel for effective data hiding within videos.…”
Section: Related Workmentioning
confidence: 99%
“…Performance comparison of the proposed technique with [6,7,32,33] has been given in Table VIII. The comparison has been made with respect to several features like imperceptibility, watermark capacity, reversibility and ratio of extra side information with the pure watermark.…”
Section: Watermark Extractionmentioning
confidence: 99%
“…They are using motion vectors for watermark embedding but they are not targeting the ultrasound videos and have not mentioned anything for the reversibility of the original content. In this paper, the proposed approach is compared with the previous approaches [6,7,32,33], where the authors are using normal/medical videos for embedding the watermarks /reversible-watermark(s). The experimental comparison shows that the proposed approach validates the usefulness of the reversible watermarking in motion vectors for the protection of an ultrasound image sequence.…”
Section: Watermark Extractionmentioning
confidence: 99%
“…Compared to the image case, there exist limited studies for reversible video watermarking. Prediction error between consecutive frames is utilized in [7] and [8] while interpolation error is used in [9]. A new data hiding method called recursive histogram modification is applied on video sequences in [10].…”
Section: Introductionmentioning
confidence: 99%